2nd Water Cisterns: Social technologies promoting adaptive capacity to Brazilian family farmers - Cavalcante, Louise; Mesquita, Patrícia S.; Rodrigues-Filho, Saulo (Desenvolvimento e Meio Ambiente, 2020)